Network analysis for performance control in the governance of interconnected local transport companies - Tampieri, Laura; Canonico, Paolo (International Journal of Strategic Property Management, 2018)
This paper discusses a network-analysis approach to the performance control of integrated built-environment systems based on efficiency, effectiveness, and adequacy. We apply this perspective to the governance of systems of local transport companies in built environments, which are frequently organized as networks. To this end, we propose a multi-dimensional grid of first- and second-order ties to locate network units and individuate the adequacy or appropriateness of network structures for performance control. In this field, issues connected to transport systems such as sustainability play a crucial role in defining structures and processes of network performance control. We empirically examine a pilot case of local public transport companies in the Forlì-Cesena area (Italy), testing network adequacy and giving evidence for the optimal localization of governance among units dedicated to providing transport services. Our results also support the hypothesis that, although structural centralization was ostensibly oriented towards increasing governance, the structure actually devolved into decentralized control at the periphery of the network, diminishing the effectiveness of initiatives.